The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.33650/al-tanzim.v5i2.2014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Education and Training Program at Medan Religious Training Center

Abstract: This study aims to analyze and evaluate the context, input, process, and product of a substantive technical training program for preparing lesson plans for Madrasah Ibtidaiyah teachers. The study used a qualitative approach with the CIPP evaluation model (context, input, process, and product). The results showed that; first, the context dimension states that the implementation of education and training is by the legal basis for working; second, the input dimension includes the availability of reliable resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…e. Assisting the development of the overall direction and strategy of the organization, taking into account HR aspects. f. Assist and create conditions that can assist line managers in achieving goals (Ali & Harahap, 2021). It was concluded that human resource management is a system that manages human resources so that they can be used effectively and efficiently to achieve certain company-owned goals (Ozkeser, 2019).…”
Section: Human Resource Managementmentioning
confidence: 99%
“…e. Assisting the development of the overall direction and strategy of the organization, taking into account HR aspects. f. Assist and create conditions that can assist line managers in achieving goals (Ali & Harahap, 2021). It was concluded that human resource management is a system that manages human resources so that they can be used effectively and efficiently to achieve certain company-owned goals (Ozkeser, 2019).…”
Section: Human Resource Managementmentioning
confidence: 99%
“…Supervisi merupakan suatu pelayanan yang disiapkan oleh seorang pemimpin dalam memberikan bantuan terhadap guru agar supaya menjadikan guru professional, cakap serta terampil seiring perkembangan ilmu dan teknologi sekarang ini (Kusumawati, 2016;Munawar, 2019;Hefniy et al, 2020;Aryani et al, 2021). Peran guru selaku tenaga pendidik pada unsur pendidikan sangat berpengaruh terhadap keefektifan penyeleggaraan pendidikan di PAUD dalam mengembangan kompetensi anak (Harimurti, 2019;Ali & Harahap, 2021), khususnya bahasa reseptif yang menjadi fokus kajian pada penelitian ini. Pengembangan bahasa pada anak usia dini melibatkan aspek sensori motor terkait dengan kegiatan mendengar, kecakapan memahami, dan produksi suara (Alfin & Pangastuti, 2020).…”
Section: Pendahuluanunclassified